Faktor-Faktor Yang Mempengaruhi Tax Avoidance pada Perusahaan Barang Konsumsi di Indonesia - Stefanie Lucy Wirawan; Yuniarwati (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2022)
The main purpose of this research is to analyze the effect of profitability, leverage, firm size and corporate social responsibility towards tax avoidance on the consumer goods manufacturing companies listed on the Indonesia Stock Exchange (IDX) during 2018-2020. The data in this study uses secondary data in the form of financial statement and annual report obtained from IDX’s official website (www.idx.co.id) and the official websites of each company. The sample was selected using the purposive sampling method in order to obtain 29 companies. This study used Eviews 12 and Microsoft Excel 2019 to process the data. This study uses descriptive statistical analysis, classical assumption test, and multiple linear regression test. The results of this study indicate that profitability and leverage have no significant effect on tax avoidance, while firm size and corporate social responsibility have a negative and significant effect on tax avoidance.